Black and white ball [large type] - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels., 2018)
"Detroit hit man Peter Macklin forces private eye Amos Walker to furnish protection for Laurie, Macklin's estranged wife, while Macklin tracks down the party who has threatened to kill her. The man Walker's client suspects cannot be ignored; as his own grown son, Roger Macklin has inherited all the instincts, and acquired all the training, necessary to carry out his threat. Told partly by Walker in first-person and partly by Macklin in third, Black and White Ball places the detective squarely between two remorseless killers, with death waiting whether he succeeds or fails"--